The influence of genetic and environmental factors on the incidence of prostate cancer in men - Olko, Paweł; Licak, Gabriela; Tomkiewicz, Julia; Tomkiewicz, Michał; Paluch, Michał; Sałata, Piotr; Żuchnik, Magda; Radulski, Jakub; Szczuraszek, Hugo; Bętkowska, Paulina; Dadziak, Mikołaj (Journal of Education, Health and Sport, 2023)
Introduction The prostate gland is a small reproductive organ found in men. It consists of 3 zones: central, peripheral and transitional. The most common localization of prostate cancer in elderly men is the peripheral zone. Prostate cancer is one of the most common cancers in men. It ranks second in terms of incidence and fifth in terms of lethality among men worldwide. There are many factors that contribute to the development of prostate cancer in men. We can divide them into two large groups: genetic factors and environmental factors. These include, among others: older age, ethnicity / race, positive family history, genetic predisposition, type of diet, obesity, smoking or higher height. Each of the above factors has a different impact on the incidence of prostate cancer, which has been demonstrated on the basis of the results of numerous studies and will be summarized in the following review. Materiał and Methods This review was based on available data collected in the PubMed database, using the following keywords: „Prostate Cancer”, „Epidemiology of Prostate Cancer” and „Risk factors of Prostate Cancer”. Conclusions Prostate cancer is a serious problem affecting men all over the world. Every year we observe an increasing incidence of this disease, which makes prostate cancer one of the most common cancers affecting men. There are many factors affecting the occurrence of this cancer, but it is extremely difficult to study their exact impact on the development of prostate cancer. Therefore, new initiatives and research should be undertaken to broadly understand the etiology and risk factors of this cancer.